Decreasing sense of coherence and its determinants in spousal caregivers of persons with mild Alzheimer's disease in three year follow-up: ALSOVA study. (July 2014) - Välimäki, Tarja; Martikainen, Janne; Hongisto, Kristiina; Fraunberg, Mikael; Hallikainen, Ilona; Sivenius, Juhani; Vehviläinen-Julkunen, Katri; Pietilä, Anna-Maija; Koivisto, Anne M.; (For the ALSOVA Study Group)
ABSTRACT Background: Sense of coherence (SOC) is associated with the capability to cope with caregiving. Our aims were (1) to describe the trajectory of SOC in aged spousal caregivers of persons with mild Alzheimer's disease (AD) in 3-year follow-up and (2) to identify baseline determinants influencing SOC change. Methods: Both AD (n = 170) (CDR-SOB, MMSE, NPI, ADCS-ADL) and caregiver- (n = 170) (BDI, SOC) related efficacy parameters were evaluated annually. Follow-up time was 3 years. The relationship of potential baseline factors with longitudinal SOC was analyzed using linear mixed models. Results: The mean drop-out-adjusted SOC score (148.5 at baseline) was decreased by 4.56 points (p = 0.002) during the follow-up. Caregivers' depression at baseline predicted the significant decrease of SOC (every + 1 BDI point decreases 2.181 points in SOC, p = 0.0001). When caregiver's depression was not taken into account in the analysis, female gender, and higher age and AD patient's lower baseline MMSE were associated significantly (p < 0.05) with decreasing SOC score in the follow-up. Other studied covariates were not associated with SOC change. Conclusions: SOC is not as stable as expected, but decreases during long-lasting caregiving. Caregiver's depression at baseline predicts SOC decrease over time. In the future, caregiver dependent factors should be evaluated at the beginning of caregiving to target individualized support programmes to the vulnerable caregivers.